Case Based English Learning for Enhancing Public Policy Analysis - Abdul Rahman; Gunawan Gunawan; Mardi Mardi; Heri Afian; Zainal Zainal (Jurnal Studi Guru dan Pembelajaran, 2025)
This study explores how the integration of Case-Based Learning (CBL) and English for Specific Purposes (ESP) enhances students’ analytical, linguistic, and reflective competencies in public policy analysis within the Public Administration Study Program at Cahaya Prima Bone University. Students' poor academic English proficiency in public administration and their incapacity to critically examine policies served as the driving forces behind the study. the objective of this research is to design, implement, and evaluate the effectiveness of a Case-Based English Learning model tailored to public policy analysis. Utilizing a qualitative methodology with a descriptive design , the study involved first-semester Public Administration students at Universitas Cahaya Prima Bone, selected using a purposive sampling technique. Data were gathered through direct observation, in-depth interviews with students and lecturers, and document analysis. Analysis was conducted interactively using data reduction, data presentation, and inductive conclusion drawing.The results show that when Case-Based Learning (CBL) and English for Specific Purposes (ESP) are combined, students' critical thinking, academic literacy, and contextual understanding of public policy are all significantly enhanced, and their interpersonal and collaborative abilities are also fostered. Group case study and classroom discussions were identified as the most successful activities, encouraging participation and peer interaction. However, a number of issues surfaced, such as differences in English language ability and a lack of time for in-depth conversations on difficult subjects. Despite these drawbacks, lecturers and students concurred that the Case-Based Learning approach effectively links linguistic competency and analytical reasoning. In conclusion, Case-Based English Learning is a pedagogical innovation that supports the development of graduates in public administration who are globally competent by linking language learning with professional policy analytic skills. It is advised that future studies apply this paradigm to other non-linguistic fields in order to investigate its wider pedagogical and institutional implications.